English Extensive Reading Material Needs in Digital Era - Nurul Lailatul Khusniyah (STAI Hubbulwathan Duri, 2021)
Material is the main needs for the teaching and learning process. Advanced technology has influenced the paradigm of material presenting. This study was to identify material needs for English extensive reading course in the digital era. The study used a qualitative approach through the descriptive qualitative method. Data is taken from observation, interview, and questionnaire. Data validity used triangulation and analysis data used data reduction, data display, and taking conclusion. The findings concluded that the need 0f teaching materials for learning extensive reading in English must be under the curriculum so that students can answer global challenges, the industry, technological developments, and changes in human life that continue to develop. The presentation of the material is also directed at implementing digital facilities that are easily accessible to students. The results of the study also have implications for exploring the ability to read digital sources and variations of material according to student needs or globalization competition.